Partisipasi Politik Generasi Milenial Di Kota Baubau Dalam Pemilihan Umum Anggota Legislatif Tahun 2024 - La Ode, Yasin; La Ode Abdul, Munafi; Wa Ode, Rohmiati M. (LeRIn - Universitas Dayanu Ikhsanuddin - Prodi. Sosiologi, 2025)
This study aims to analyze the forms of political participation of the millennial generation in Baubau City during the 2024 Legislative Election and to identify the factors influencing their engagement. Employing a descriptive qualitative approach, data were collected through in-depth interviews with informants consisting of legislative candidates, city council members, polling station officials (KPPS), local entrepreneurs, and university students. The data were analyzed using three models of voter behavior: sociological, psychological, and rational choice. The findings reveal that millennials’ participation encompasses both electoral and non-electoral spheres, including running as legislative candidates, serving as KPPS members, participating in campaigns, engaging in political discussions, and exercising their voting rights. Media exposure—particularly through social media—and rational evaluation of candidates’ vision and mission emerged as the most decisive factors, while family influence and candidate popularity appeared comparatively weak. These findings suggest that the political behavior of Baubau’s millennial generation is increasingly driven by digital information flows and rational calculation, reflecting a form of political engagement that is critical, adaptive, and closely aligned with the dynamics of contemporary local democracy.